2018
DOI: 10.18203/2320-6012.ijrms20180284
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of hematological profile on presentation in confirmed cases of malaria, dengue and leptospirosis

Abstract: Background: Malaria, leptospirosis and dengue fever are the predominant monsoon related illnesses in the Indian subcontinent causing considerable mortality and morbidity. These have similar clinical profile and derangement in one or more haematological parameters. We have studied the haematological profile at presentation to differentiate one infection from the other as it presents a significant diagnostic challenge to the treating physician.Methods: A prospective observational study of haematological profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…11 Vaidya MS et al, study showed more than the double ratio of incidence of malaria in males compared to females. 12 In present study most commonly affected age group is 21-40, which contributes to 65% of total patients. The percentage of patients affected aged above 60 is 9%.…”
Section: Discussionmentioning
confidence: 64%
“…11 Vaidya MS et al, study showed more than the double ratio of incidence of malaria in males compared to females. 12 In present study most commonly affected age group is 21-40, which contributes to 65% of total patients. The percentage of patients affected aged above 60 is 9%.…”
Section: Discussionmentioning
confidence: 64%
“…In Vaidya MS et al, study it was about 27.3%. 11 Arevalo Herrera et al had 19.7% and Rathod SN et al, had 27.3% of anemia incidence in their studies. 12 The percentage of incidence of severe anemia (7gm/dl) in our present study is 20% most of which is due to falciparum infection malaria compared to vivax malaria.…”
Section: Discussionmentioning
confidence: 89%
“…73.01% of the patients with spleenomegaly had thrombocytopenia (Table 2). (11) and in mixed infection 100% (2). Lymphopaenia was observed in 13% ( 13) of total patients.…”
Section: Figure 1: Incidence Of Different Species Of Malariamentioning
confidence: 99%